BASIC ASPECTS OF SECESSION IN THE CASE OF MONTENEGRO - Krnetic, Helena (Politeia, 2019)
In this analysis, we will try to look at the relevant aspects of the case of Montenegro's independence, its historical assumptions, relevant political factors, with particular emphasis on the analysis of the year in which the referendum was held. The secession of Montenegro represented the final act of its accomplished status within the Yugoslav state. The contradiction of Montenegro's unification to Serbia in 1918 following the decisions of the Podgorica Assembly resulted in the emergence of a secessionist movement in Montenegro. The people of Montenegro expressed their right to self-determination in different ways, because one part wanted unification with Serbia, the other part advocating for the establishment of Montenegro as an independent state. The secessionist movement is an expression of the negative self-determination of a part of Montenegrin citizens towards the state unity with Serbia. The aim of this paper is to identify the basic elements that influenced the secession of Montenegro, especially in terms of its legitimacy and legality. The case of Montenegro's secession, as a subject of analysis, is a specific one because Montenegro used to be an independent state, with recognised international subjectivity. The political and scientific dilemma lies in the fact that this problem can be viewed through several paradigms. One starting point might be that Montenegro united as a state with the state of Serbia; the second might be that the people of Montenegro opted, expressing their free will, to live in Serbia as their common state of choice; and the third might be that the state of Serbia annexed the state of Montenegro, without respecting its constitutional and legal order.
Keywords: Montenegro; secession; self-determination; state; Constitution; legality; legitimacy